Jesus and Salvation : Soundings in the Christian Tradition and Contemporary Theology - Ryan, Robin (Book collections on Project MUSE., 2015)
How does the Christian proclamation of salvation in Jesus Christ relate to the lives of the people who suffer most? Does salvation consist entirely of the hope for eternal life with God? How might the church effectively preach the message of salvation in Christ today? In Jesus and Salvation, Robin Ryan adopts a historical approach to these questions, discussing key themes and classic authors in the developing tradition about Christ the Savior. He examines modern soteriology by engaging the thought of Karl Rahner, Edward Schillebeeckx, Gustavo Gutierrez, and Elizabeth Johnson. He also discusses contemporary conceptions of salvation within an evolutionary view of the cosmos as well as issues related to the Christian confession of Jesus as universal savior in a religiously pluralistic world. Ryan concludes by offering his own reflections on the meaning of salvation from God in Jesus Christ. By understanding salvation in Christ as both gift and call, Ryan invites readers to recognize in the saving grace of God a responsibility for the well-being of the human family and the rest of creation.